HISTORY OF FORMATION AND STAGES OF DEVELOPMENT OF SURKHANDARYA RESERVOIRS - Makhmatkulova Nozikoy Choriyevna (Western European Studies, 2025)
This article analyzes the formation of reservoirs in the Surkhandarya region, the stages of their construction, and their historical development. The study highlights major irrigation projects implemented in the region since the mid-20th century, the policies aimed at developing water management, and the significance of reservoirs in agriculture and the socioeconomic life of the region. Additionally, the article examines the technical solutions applied during the construction of the South Surkhan, Tupalang, Uchkizil, Oktepa, and Degrez reservoirs, as well as the natural-geographical factors and their impact on the region’s ecology. Based on historical, geographical, and analytical methods, the research investigates the stepby-step formation of the Surkhandarya reservoir system and scientifically substantiates its current state and development prospects.
Keywords: reservoir; irrigation; historical development